Pelaksanaan Praktik Kemahiran Hukum II di Bagian Hukum Sekretariat Kota Palangka Raya - Muhammad Maulana Nazril; M. Faishal Fadhlurrahman; Fayzah Nazmah; Novita Ayu Fitri Wulandari; Muhammad Aulia Rahman; M. Luthfi Setiarno Putera (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the organizational structure, main tasks and functions, and challenges faced by the Legal Section in carrying out its role as a center for local government legal services. The research method used a qualitative approach through interviews with the Head of the Legal Section, direct observation in the work environment, and literature studies of various related documents and regulations. The results of the study indicate that the organizational structure of the Legal Section consists of functional positions, implementing officers, and temporary employees, each of which has a crucial role in supporting the legal product drafting process. However, the effectiveness of organizational performance still faces obstacles, particularly related to employee discipline, work ethic, and efforts to build a culture of bureaucratic integrity. The Head of the Legal Section emphasized that the quality of human resources is a key factor in determining the success of the process of harmonization of regulations and legal services. Thus, a sustainable apparatus development strategy and strengthening of the work system are needed so that the Legal Section can carry out its functions optimally in supporting the implementation of the Palangka Raya City government.